The Effectiveness of Service Quality on Room Occupancy Rates at Le Meridien Bali Jimbaran - Agung Putu Swabawa, A.; Dewa Gede Ari Pemayun, I; Sugito, Sugito; Ketut Suarta, I; Idham, Idham (International Journal of Science, Technology & Management, 2026)
This study aims to determine the quality of service provided to guests staying at Le Meridien Bali Jimbaran and the effectiveness of service quality on the room occupancy rate achieved at Le Meridien Bali Jimbaran. The methods used to collect data, there are 6 methods, namely: observation, interviews, questionnaires, documentation, and literature studies. The analysis techniques used, namely: a. Quantitative Analysis, namely: 1) Analysis techniques to analyze quantitative data, using descriptive statistical techniques, namely statistical techniques that discuss the collection, processing, presentation, and calculation of values ​​​​from data described in tables or diagrams, 2) T-test for two paired samples (Paired-samples T Test) namely testing the effectiveness of service quality on hotel occupancy achievements. b) Qualitative descriptive analysis techniques to explain the results of qualitative data analysis and help draw conclusions about the research results from the process or event. Based on the analysis results, it shows that the quality of service provided to guests at Le Meridien Bali Jimbaran is very good with a value of 4.48. Meanwhile, the quality of service provided to guests has a real or significant impact on increasing the achievement of room occupancy rates at Le Meridien Bali Jimbaran, which can be seen from the calculated t (3,888) which is greater than the t-table (2,2010), which is in the rejection area of ​​Ho and H1 is accepted. This means that the quality of service provided to guests has a very effective impact on increasing the achievement of room occupancy rates at the Le Meridien Bali Jimbaran hotel.